SAT0731-HPR Symptoms of pain, fatigue and self-efficacy in young patients with spondyloarthritis – a comparison between women and men. (15th June 2017) - Torell, A; Bremander, A; Bergman, S; Haglund, E
Abstract : Background: Spondyloarthritis (SpA) often has an early disease onset with inflammatory back pain debuting already in young adulthood. Studies have shown gender differences in disease specific areas but few studies have focused only on the younger subjects. Extended knowledge based on self-reported information can help to better understand the characteristics of these younger women and men with SpA. Objectives: To study the differences between young women and men with SpA with regard to self-reported pain measures, disease activity, fatigue, self-efficacy and health status. Methods: A cross-sectional population based cohort of 201 patients age 18–36 years with SpA identified through a health care register by searching for ICD-10 codes for SpA between the years 2003–2007. They all responded to a questionnaire survey in 2009. 29% were diagnosed with ankylosing spondylitis, 39% with psoriatic arthritis, and 32% with undifferentiated spondyloarthritis. The survey included questions concerning pain (NRS 0–10 and a pain mannequin), fatigue (NRS 0–10), self-efficacy (ASES 10–100, low-high). The pain mannequin was used to categorize patients into groups; no chronic pain (NCP), chronic regional pain (CRP)or chronic widespread pain (CWP). Self-reported disease activity (BASDAI 0–10) and health status (EQ5D, 0–1) were used to describe the group. Characteristic symptoms are reported as mean, standard deviation (SD) and frequencies. T-test and Chi2 test were used to study gender differences. Results: The mean age (SD) was, 30 (5) years, 60% were women. The group reported disease activity scores (BASDAI) of 3.8 (2.3), health status 0.75 (0.16), and a disease duration of 7 (5) years. One third were smokers or former smokers, and 69% reached WHO's recommended level of health enhancing physical activity. 21% reported CRP, 41% CWP and the remaining 38% reported NCP. More women reported CWP pain than men, (48% vs. 30%, p=0.026). Women also reported worse pain compared to men, (3.9 (2.4) vs. 2.9 (2.1), p=0.001), worse fatigue (5.0 (2.6) vs. 3.9 (2.7), p=0.003), less self-efficacy for pain (53 (20) vs. 59 (21), p=0.040) and also for symptoms (59 (19) vs. 65 (20), p=0.038). Conclusions: A significant proportion of both women and men reported symptoms consistent with chronic widespread pain already at young age. Women reported in general worse health compared to men, including pain distribution, pain intensity and pain management. This information could be valuable for clinicians in the care of young patients with SpA. Disclosure of Interest: None declared